2018
DOI: 10.1007/s11051-018-4152-3
|View full text |Cite
|
Sign up to set email alerts
|

Can disc diffusion susceptibility tests assess the antimicrobial activity of engineered nanoparticles?

Abstract: The use of disc diffusion susceptibility tests to determine the antibacterial activity of engineered nanoparticles (ENPs) is questionable because their low diffusivity practically prevents them from penetrating through the culture media. In this study, we investigate the ability of such a test, namely the Kirby-Bauer disc diffusion test, to determine the antimicrobial activity of Au and Ag ENPs having diameters from 10 to 40 nm on Escherichia coli cultures. As anticipated, the tests did not show any antibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…AgNPs display a low-activity ZoI, particularly against Gram-negative bacteria. It has been reported that metal nanoparticles tend to form agglomerates when in colloidal dispersions, which reduces their diffusivity, limiting the contact with the bacteria [37]. Here, the presence of agglomerates is evident (Figure 1), supporting this statement.…”
Section: Agar-well Diffusionsupporting
confidence: 80%
“…AgNPs display a low-activity ZoI, particularly against Gram-negative bacteria. It has been reported that metal nanoparticles tend to form agglomerates when in colloidal dispersions, which reduces their diffusivity, limiting the contact with the bacteria [37]. Here, the presence of agglomerates is evident (Figure 1), supporting this statement.…”
Section: Agar-well Diffusionsupporting
confidence: 80%
“…Also, Gram-negative E. coli was not inhibited at all. However, some NPs report lower diffusivity through the agar media, and their reduced penetration causes the limitation of diffusion technique [ 66 ]. Therefore, for the evaluation of these findings, fluorescence microscopy of bacterial cells obtained from these scaffolds was performed ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Kirby-Bauer disk diffusion method relies on the diffusion of the test substance from a sterile paper disk to bacterial cultures. Thus, this result might be affected by the diffusion rate of particles as metal nanoparticles have low diffusion rate as compared to standard antibiotics ( Kourmouli et al., 2018 ). As a consequence, metal nanoparticles do not travel far from deposition disks to interact physically with the bacterial cells.…”
Section: Resultsmentioning
confidence: 99%